STATEGI PENANGGULANGAN KEMISKINAN (STUDI KASUS DKI JAKARTA) - Bambang Giyanto (Puslatbang KDOD Lembaga Administrasi Negara, 2008)
Poverty is one of a problem in Indonesia. As a metropolitan city, Jakarta teases people from all other regions to try their fortune there. Some people can make it and be success, but some others can’t achieve it because they don’t have enough skill to fight in this big city. Such problems then create loiterers, street musicians and beggars which increase year by year. Therefore, the government of DKI Jakarta Province put the law (district regulation) number 7 year 2007, about public order into effect. It is so expected that through this way, the problem of social prosperity can be put in to order. Key word: Poverty, Jakarta, Districtl Regulation